Формулы приведения для тригонометрических функций

 

cos (π + t) = –cos t

sin (π + t) = –sin t

tg (π + t) = tg t

ctg (π + t) = ctg t

cos (π – t) = –cos t

sin (π – t) = sin t

tg (π – t) = –tg t

ctg (π – t) = –ctg t

cos (2π + t) = cos t

sin (2π + t) = sin t

tg (2π + t) = tg t

ctg (2π + t) = ctg t

cos (2π – t) = cos t

sin (2π – t) = –sin t

tg (2π – t) = –tg t

ctg (2π – t) = –ctg t

cos (π/2 + t) = –sin t

sin (π/2 + t) = cos t

tg (π/2 + t) = –ctg t

ctg (π/2 + t) = –tg t

cos (π/2 – t) = sin t

sin (π/2 – t) = cos t

tg (π/2 – t) = ctg t

ctg (π/2 – t) = tg t

cos (3π/2 + t) = sin t

sin (3π/2 + t) = –cos t

tg (3π/2 + t) = –ctg t

ctg (3π/2 + t) = –tg t

cos (3π/2 – t) = –sin t

sin (3π/2 – t) = –cos t

tg (3π/2 – t) = ctg t

ctg (3π/2 – t) = tg t

 

Сделать бесплатный сайт с uCoz